Traumatic brain injury, diabetic neuropathy and altered-psychiatric health: The fateful triangle. (October 2017) - Abou-El-Hassan, Hadi; Dia, Batoul; Choucair, Khalil; Eid, Stephanie A.; Najdi, Farah; Baki, Lama; Talih, Farid; Eid, Assaad A.; Kobeissy, Firas
Abstract: Traumatic brain injury is a detrimental medical condition particularly when accompanied by diabetes. There are several comorbidities going along with diabetes including, but not limited to, kidney failure, obesity, coronary artery disease, peripheral vascular disease, hypertension, stroke, neuropathies and amputations. Unlike diabetes type 1, diabetes type 2 is more common in adults who simultaneously suffer from other comorbid conditions making them susceptible to repetitive fall incidents and sustaining head trauma. The resulting brain insult exacerbates current psychiatric disorders such as depression and anxiety, which, in turn, increases the risk of sustaining further brain traumas. The relationship between diabetes, traumatic brain injury and psychiatric health constitutes a triad forming a non-reversible vicious cycle. At the proteomic and psychiatric levels, cellular, molecular and behavioral alterations have been reported with the induction of non-traumatic brain injury in diabetic models such as stroke. However, research into traumatic brain injury has not been systematically investigated. Thus, in cases of diabetic neuropathy complicated with traumatic brain injury, utilizing fine structural and analytical techniques allows the identification of key biological markers that can then be used as innovative diagnostics as well as novel therapeutic targets in an attempt to treat diabetes and its sequelae especially those arising from repetitive mild brain trauma.